INVERTEBRATE-DERIVED ENZYMES IN FOCUS: ARAZYME'S JOURNEY INTO ANIMAL NUTRITION - Lee, JW; Yeom, EK; Choi, YJ (Research Journal of Agriculture (RJA), 2023)
Enzymes derived from the gut symbionts of invertebrates have emerged as a promising and relatively unexplored resource in the realm of biologically active molecules. These enzymes play a pivotal role in facilitating the efficient utilization of a diverse array of nutrient resources by their invertebrate hosts (Jing et al., 2020). Consequently, the field of animal husbandry has exhibited substantial interest in harnessing these invertebrate-derived bioactive enzymes to enhance various aspects of animal nutrition and health (Kannan et al., 2019). One such intriguing enzyme is Arazyme, an alkaline metalloprotease secreted by Serratia proteamaculans, a gram-negative aerobic bacterium belonging to the genus Serratia. Isolated from the intestinal ecosystem of Nephila clavate (Fig. 1), a remarkable arachnid known as "棒络新妇" in Chinese and "무당거미" in Korean (Bersanetti et al., 2005; Kwak et al., 2007), Arazyme plays a crucial role in facilitating the digestion process within Nephila clavata. This enzyme, with a molecular size of 51.5 kDa, has even gained approval as a food additive (registration No. 2007-SA-0007) from the Ministry of Food and Drug Safety in the Republic of Korea. Significantly, Arazyme exhibits exceptional enzymatic activity across a wide pH and temperature range and displays impressive resistance to detergents, enhancing its potential for industrial applications (Bersanetti et al., 2005). As an innovative invertebrate-derived bioactive enzyme, Arazyme holds immense promise in the domain of animal husbandry. This manuscript presents a comprehensive review of the current understanding and knowledge concerning Arazyme, with the primary aim of providing valuable insights and references for its prospective applications. The versatile enzymatic properties of Arazyme open doors to a myriad of potential applications, ranging from animal feed supplementation to biotechnological advancements. This review explores the characteristics, mechanisms, and potential applications of Arazyme, shedding light on its multifaceted utility in various industries. Through a comprehensive synthesis of existing research, this review paves the way for future investigations and innovations, encouraging further exploration of the diverse functionalities and applications of this remarkable invertebrate-derived enzyme